STYLISTIC SYNTHESIS AS A PROMISING METHOD OF MODERN WOMEN`S COSTUME FORMATION - Харченко, А. В. (Art and Design, 2020)
The aim of the article is to analyze the stylistic synthesis examples in the design of a modern costume, and to identify the actual combinations of two or more styles in one image which are preferred by Ukrainian designers. Models of modern women’s clothing, represented on the Ukrainian market by designers, trade locations, and printed fashion magazines has been used asthe objects of the analysis. Methodology.The systematic approach has been used for examination of the modern design activities as result of the postmodern culture influence and for detection of the relationship between artistic phenomena and the design practice. Art analysis has been used for the analysis of the shape, silhouette, costume plasticity, and allowed to reveal the main ways of different styles elements combination into a single structural integrity. Resalts. The interpretation of the different styles interaction problem in art and dsign by art theorists and costume practitioners has been given in the study. The analysis of women's clothing models represented on the Ukrainian market by such designers as Nadya Dzyak, Ksenia Schnaider, and such Ukrainian brands as RITO, Jul through the Ukrainian Fashion Week web-resource, own web-sites and online stores, and published by TRserial and ELLE has been provided. The fact that modern costume designers are vibrantly trying to combine components ofdifferent styles in one image, which allows obtaining a variety that reflects a wide range of human needs and preferences, has been demonstrated. Scientific novelty. The study of stylistic synthesis as a separate direction in the costume design has been represented. The visual series that allows studying of the stylistic combinations variability and identifying the need of stylistic synthesis introduction into the theory and practice of design techniques have been formed with the help of the selective method. The main directions of different styles synthesis in the designers developments have been determined. The practical significance. The analysis of stylistic synthesis promising techniques in the modern women's costume can supplement the insufficiently studied areas in the theory and practice of design. The results of the study can be used as practical recommendations for costume design and fashionable image formation based on the stylistic synthesis.